2017
DOI: 10.1186/s13756-017-0288-7
|View full text |Cite
|
Sign up to set email alerts
|

The common enteric bacterial pathogens and their antimicrobial susceptibility pattern among HIV-infected individuals attending the antiretroviral therapy clinic of Hawassa university hospital, southern Ethiopia

Abstract: BackgroundThe frequent occurrence of bacterial gastroenteritis among HIV-infected individuals together with increased antimicrobial drug resistance pose a significant public health challenge in developing countries. This study aimed to determine the prevalence of enteric bacterial pathogens and their antimicrobial susceptibility pattern among HIV-infected patients in a tertiary hospital in southern Ethiopia.MethodsA hospital-based cross-sectional study was conducted at Hawassa University Comprehensive Speciali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 20 publications
10
23
0
Order By: Relevance
“…In the present study, HIV-infected individuals who had a CD4 + count <200 cells/µL was 3.6 times more likely found to be infected with NTS bacteria (AOR: 3.61, 95% CI: 1.74–5.25). This finding was in agreement with other studies conducted elsewhere,8,26,30 suggesting unfavorable immunological and virological responses contributed to increased risk of NTS bacteremia.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, HIV-infected individuals who had a CD4 + count <200 cells/µL was 3.6 times more likely found to be infected with NTS bacteria (AOR: 3.61, 95% CI: 1.74–5.25). This finding was in agreement with other studies conducted elsewhere,8,26,30 suggesting unfavorable immunological and virological responses contributed to increased risk of NTS bacteremia.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, a lack of hand washing habit before food preparation was found to increase the odds of acquiring NTS bacteremia (AOR:13.1, 95% CI: 10.40–15.30). This was inconsistent with the study conducted in Hawassa University Hospital, southern Ethiopia 30. Health education regarding personal hygiene, hand washing before and after food preparation, surveillance of NTS infection, and isolation of identifying cases are possible solutions for prevention and control of NTS bacteria 11…”
Section: Discussionmentioning
confidence: 87%
“…The rate of Enterobacteriaceae isolates in the present study from stool sample of HIV infected individuals was shown to be 12.5%. Previous studies reported similar rates of; 12.6% in southwest Ethiopia [31], 12.5% in Cambodia [32] and 14.5% in Peru [33]. However, rates reported in Uganda (19.2%) [34], in India (29%) [35], in Southwest Ethiopia (Jimma) (16%) [36] and South Africa (43.3%) [37] were higher than our ndings.…”
Section: Discussionsupporting
confidence: 57%
“…2 ). In this meta-analysis, the lowest prevalence was 6.1% [ 29 ] from stool sample of HIV infected individuals and highest prevalence was 72.7% from cloacal samples of chicken [ 11 ]. The Campylobacter species including C. jejuni, and C. coli (C. lari in few studies too) were reported at species level in 75% of the studies.…”
Section: Resultsmentioning
confidence: 99%